Hybrid anisotropic materials for structural aviation parts - Golfman, Yosif (CRC Press, 2011)
Optimization of aviation and space vehicle design requires accurate assessment of the dynamic stability and general properties of hybrid materials used in aviation parts. Written by a professional with 40 years of experience in the field of composite research, Hybrid Anisotropic Materials for Structural Aviation Parts provides key analysis and application examples to help the reader establish a solid understanding of anisotropic properties, theory of laminates, and basic fabrication technologies. Tools to ensure cost-effective, optimized fabrication of.